2019
DOI: 10.1007/s10461-019-02715-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy is Not Everything: Eliciting Women’s Preferences for a Vaginal HIV Prevention Product Using a Discrete-Choice Experiment

Abstract: As new female-initiated HIV prevention products enter development, it is crucial to incorporate women's preferences to ensure products will be desired, accepted, and used. A discrete-choice experiment was designed to assess the relative importance of six attributes to stated choice of a vaginally delivered HIV prevention product. Sexually active women in South Africa and Zimbabwe aged 18-30 were recruited from two samples: product-experienced women from a randomized trial of four vaginal placebo forms and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
1
19
4
Order By: Relevance
“…Nineteen studies examined PrEP [ 33 , 34 , 36 , 40 , 43 , 46 , 49 , 51 , 61 , 64 66 , 70 , 71 , 78 , 79 , 83 , 90 , 91 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen studies examined PrEP [ 33 , 34 , 36 , 40 , 43 , 46 , 49 , 51 , 61 , 64 66 , 70 , 71 , 78 , 79 , 83 , 90 , 91 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…In studies that considered the vaginal ring, the ring rated poorly compared with other formulations, and was sometimes the least preferred [ 33 , 34 , 51 , 64 , 83 ]. Other product attributes included side effects, efficacy, additional protection from pregnancy or STI (pregnancy prevention was valued; STI prevention was valued among female sex workers [FSW]) [ 46 , 49 , 83 ]; and changes to menstruation [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Interestingly, although women continue to have high rates of HIV acquisition in Sub-Saharan Africa, the majority were willing to exchange higher effectiveness for other desired attributes (such as the impact on vaginal wetness, pregnancy prevention and dosing regimen), according to a study of women in South Africa and Zimbabwe. 45 Research has shown that the perceptions of effectiveness among target populations influence the acceptance and in turn, the uptake of biomedical interventions. 46 Therefore, wider promotion of PrEP's high effectiveness may attract people to consider PrEP.…”
Section: Reviewmentioning
confidence: 99%
“…We described methods of long-acting HIV prevention currently pending regulatory approval or in development, and asked participants about preferences regarding HIV prevention modalities that may be available in the future. We adapted a list of PrEP characteristics from a discrete choice experiment of HIV prevention methods assessed within the Quatro Study [30]. We asked participants to rank the top three most important characteristics of a potential HIV prevention product, the top three most important accessrelated characteristics, and how frequently they would theoretically use an HIV prevention method.…”
Section: Current and Future Prep Preferencesmentioning
confidence: 99%